Apparent Low‐Velocity Belt in the Shallow Anninghe Fault Zone in SW China and Its Implications for Seismotectonics and Earthquake Hazard Assessment. Issue 3 (4th March 2023) - Luo, Song; Yao, Huajian; Wen, Jian; Yang, Hongfeng; Tian, Baofeng; Yan, Mengxuan
Abstract: The Anninghe fault forms the eastern boundary of the Sichuan‐Yunnan block in Southwest China and has been identified as an earthquake gap zone. This study intends to construct the upper crustal shear wave velocity ( Vs ) structure beneath the Anninghe fault to understand its seismotectonics and potential large earthquake hazards. We deployed a dense seismic array along the southern central Anninghe fault valley. From the 3‐month continuous records, we calculated vertical‐component cross‐correlation functions (CCFs). However, the surface wave signals in the CCFs are intensely interfered by near zero‐time‐lag noise. We proposed a mode separation method based on the high‐resolution linear Radon transform, which suppressed the interfered noise and greatly enhanced the surface wave signals for ambient noise tomography of the Vs structure. The fine upper crustal structure reveals a distinct narrow low‐velocity belt within a depth of 3 km beneath the Anninghe fault zone. At deeper depths (4.5–8 km), the narrow low‐velocity belt shifts to the east and correlates with the distribution of local earthquakes. Combining previous results with our new findings, we presented a seismotectonic model of the southern central Anninghe fault, which interprets the narrow low‐velocity belt as a water‐contained fracture zone that forms a seismogenic zone at deeper depths under transpression. In addition, we demonstrated through scenario earthquake simulations that fine structures play a significant role in the assessment of earthquake hazards along the Anninghe fault. As such, this study provides a typical window into seismotectonics and large earthquake hazards in the active southeastern Tibetan Plateau. Plain Language Summary: The Anninghe fault is located in Southwest China, and it has experienced a series of large earthquakes ( M  ≥ 7) during its history. However, the Anninghe fault has been silent for nearly 30 years; it has been suggested that there is a high risk of large earthquakes occurring there. To investigate the deep structural background and potential earthquake hazards associated with the Anninghe fault zone, we deployed a dense seismic array along this fault zone. During data processing, we proposed a method to eliminate coherent noise and enhance the signals considerably, which is essential for the subsequent tomography of the structures underneath. The final tomographic model shows that the Anninghe fault zone has a distinctively low seismic wave speed at shallow depths and dips to the east at deeper depths. As this observation agrees with the distribution of local earthquakes and previous findings, it may indicate the existence of a seismogenic zone capable of generating earthquakes. Additionally, we further demonstrated through simulations of large earthquakes that the high‐resolution model developed in this study is important for assessing earthquake hazards along the Anninghe fault. Key Points: A mode separation technique is proposed to suppress near zero‐time‐lag noise in cross‐correlation functions for ambient noise tomography The fine upper crustal Vs model reveals an apparent low‐velocity belt consistent with local earthquakes beneath the Anninghe fault zone Scenario earthquake simulations highlight the significance of fine structures in assessing large earthquake hazards